Comparing onsite electronic survey distribution methods. (March 2021) - Zhang, Hongchao; Groshong, Lisa; Stanis, Sonja Wilhelm; Morgan, Mark
Highlights: Compares two onsite Electronic survey distribution methods Discusses effectiveness of onsite electronic surveys Offers important methodological guidance for tablet-based survey research